Fault Tolerant Control of Robot Manipulator with Actuator Effectiveness Adaptation - Anisa Ulya Darajat; Swadexi Istiqphara; Heriansyah; Mohammad Farhan Ferdous; Abu Saleh Musa Miah; Uri Arta Ramadhani; Hari Maghfiroh (Peneliti Teknologi Teknik Indonesia, 2026)
This study discusses the implementation of fault-tolerant control (FTC) for a planar two-degree-of-freedom (2DoF) robot manipulator experiencing actuator loss of effectiveness. Several methods have been proposed, such as PID and MRAC; however, their accuracy still needs improvement. Meanwhile, FT-SMC offers high accuracy, but its methodological complexity results in longer execution time and reduced computational efficiency. The objective of this research is to develop a fault-tolerant control method that can maintain system performance under actuator degradation while achieving high tracking accuracy with improved computational efficiency. Simulations are performed with a two-link manipulator model with sinusoidal reference trajectories. An actuator fault is introduced at 4 s by reducing the actuator effectiveness to [0.5, 0.7]ᵀ, meaning that the actuator capability decreases to 50% and 70% of its nominal performance, respectively. The simulation results show that the proposed FTC controller maintains good tracking performance after the fault occurs. In contrast, the controller without FTC experiences performance degradation characterized by phase lag and amplitude attenuation in the system response. Furthermore, the actuator effectiveness estimation mechanism demonstrates fast convergence after the fault occurs, with settling times of approximately 0.084 s and 0.238 s for the first and second joints, respectively. The steady-state MAEs are 0.0080 and 0.0395, equivalent to relative errors of 1.6% and 5.6%, respectively. Compared with other FTC methods, the proposed FTC controller also provides a balanced trade-off between tracking accuracy, robustness under fault conditions, and computational efficiency, making it suitable for real-time implementation.